(untitled) (INSTITUTIO : Jurnal Pendidikan Agama Kristen, 2020)
This article aims to describe the development of counseling learning methods through ethnographic study. The chosen research location is Latuhalat, where the location is considered to be a place for developing counseling learning methods through ethnographic studies of Christian Guidance and Counseling students with the community because at this location there are several problems faced by the community related to their culture that require counselors. The informants selected were 10 second semester Christian Guidance and Counseling Study Program students in the even semester semester of Academic Year 2018/2019 at the Ambon IAKN Christian Education Faculty who were in anthropology courses and were considered to be able to represent their friends in providing their understanding related to research focus. The research method used is qualitative with in-depth interviews and observation techniques to describe or describe the facts or circumstances or symptoms that appear in the counseling process between counselor and client. The data obtained shows how students’ perceptions of guidance and counseling on ethnographic studies can bring them closer to the community and understand the problems faced by the community more clearly and the output of applying counseling learning methods through ethnographic studies at the Faculty of Christian Education IAKN Ambon can be more intertwined emotional closeness between lecturers and students because together they are directly involved in the data collection process. Keywords: development of counseling learning methods, ethnographic studies, anthropology.